Pengaruh Promosi Media Situs Jual Beli Online Terhadap Peningkatan Penjualan Produk UKM - Sovania, Erina; Selliamanik, Irma (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2019)
SME products are small and medium scale local industries that must be intensely supported by their development because these local products can raise the standard of living of people in a suburban area of ​​a large or rural city to become an independent community. This study aims to open up a broad view that for SME products it is necessary to carry out extensive sales promotions so that their products can be wellknown and sales can penetrate a wider market. The research conducted is to conduct quantitative research methods, with data collection methods through questionnaires and interviews through respondents as many as 50 online shops in bukalapak.com then the data is processed and analyzed using Pearson Product Moment Correlation (PPM) data analysis techniques to determine how big is the relationship, the Determinant Coefficient to find out the contribution of the X variable to the Y variable and the Significance Test to find out the Meaning of the Relationship in both variables, and linear regression. From the results of this study it was found that the promotion of online media buying and selling sites has a strong relationship and has a high influence on the increase in sales of SME products. Where obtained PPM correlation (relationship) of 0.75 included in the criteria for a strong relationship, and the coefficient of determinant which means that the contribution of variable X to Y has a high or strong influence, and the significance test with interpretation has the meaning of an influential relationship, and with linear regression that is y = 0.5467x - 3.4702.